Uncertain soil moisture feedbacks in model projections of Sahel precipitation. Issue 12 (17th June 2017) - Berg, Alexis; Lintner, Benjamin R.; Findell, Kirsten; Giannini, Alessandra
Abstract: Given the uncertainties in climate model projections of Sahel precipitation, at the northern edge of the West African Monsoon, understanding the factors governing projected precipitation changes in this semiarid region is crucial. This study investigates how long‐term soil moisture changes projected under climate change may feedback on projected changes of Sahel rainfall, using simulations with and without soil moisture change from five climate models participating in the Global Land Atmosphere Coupling Experiment‐Coupled Model Intercomparison Project phase 5 experiment. In four out of five models analyzed, soil moisture feedbacks significantly influence the projected West African precipitation response to warming; however, the sign of these feedbacks differs across the models. These results demonstrate that reducing uncertainties across model projections of the West African Monsoon requires, among other factors, improved mechanistic understanding and constraint of simulated land‐atmosphere feedbacks, even at the large spatial scales considered here. Plain Language Summary: Climate model projections of Sahel rainfall remain notoriously uncertain; understanding the physical processes responsible for this uncertainty is thus crucial. Our study focuses on analyzing the feedbacks of soil moisture changes on model projections of the West African Monsoon under global warming. Soil moisture‐atmosphere interactions have been shown in prior studies to play an important role in this region, but the potential feedbacks of long‐term soil moisture changes on projected precipitation changes have not been investigated specifically. To isolate these feedbacks, we use targeted simulations from five climate models, with and without soil moisture change. Importantly, we find that climate models exhibit soil moisture‐precipitation feedbacks of different sign in this region: in some models soil moisture changes amplify precipitation changes (positive feedback), in others they dampen them (negative feedback). The impact of those feedbacks is in some cases of comparable amplitude to the projected precipitation changes themselves. In other words, we show, over a subset of climate models, how land‐atmosphere interactions may be a cause of uncertainty in model projections of precipitation; we emphasize the need to evaluate these processes carefully in current and next‐generation climate model simulations. Key Points: Feedbacks on projected Sahel rainfall from long‐term soil moisture changes significantly impact precipitation projections in climate models Feedbacks on climate model projections of Sahel rainfall from long‐term soil moisture changes vary in sign across models These results call for further assessment and evaluation of soil moisture‐atmosphere interactions across current‐generation climate models